About Face: Evaluating and Managing Tactile Impairment at the Time of Autism Diagnosis. (28th October 2015) - Silva, Louisa M. T.; Schalock, Mark; Gabrielsen, Kristen R.
Abstract : Evaluation for sensory impairment is a routine part of autism diagnosis. Sensory impairment of hearing, vision, or touch results in developmental delay and must be addressed before delay can resolve. Recent studies confirm that tactile impairment is present in autism and can be effectively treated with a tactile stimulation protocol. The research suggests a change in management at the time of autism diagnosis to include evaluation and treatment of tactile impairment. Here we validate screening and management tool for tactile impairment, the Autism Touch and Self-Regulation Checklist, in 404 typical and autistic preschool children. The tool assesses tactile impairment by location and severity. Autistic children were distinguished by mixed pain and numbness on multiple areas including the face and mouth (F = 412.1 (1, 402); p < . 000 ). Oral-facial tactile impairment interferes with the tactile stimulus to orienting. We hypothesized that oral-facial tactile impairment and difficulty orienting are predictive of ASD and that severity of tactile impairment is predictive of severity of ASD. Questions evaluating oral-facial and orienting responses correctly predicted 91% of the autism group. Severity of tactile impairment correctly predicted 81% of mild versus severe ASD. Results underscore the importance of evaluating and treating tactile impairment at the time of autism diagnosis.